From sample to rapid DNA and eDNA identification: an easy step-by-step guide - Boza, Beatriz Rochitti [UNESP]; Bunholi, Ingrid Vasconcellos; Charvet, Patricia; Cruz, Vanessa Paes da [UNESP]; Alvarenga, Marcela Maki (Universidade Estadual Paulista (Unesp), 2025)
This e-book translates and expands the knowledge from Alvarenga & Bunholi et al. (2025), “Rapid DNA/eDNA-Based ID Tools for Improved Chondrichthyan Monitoring and Management”. It aims to make the methodologies, workflows, and practical guidance on rapid DNA and eDNA-based identification more accessible to researchers, students, and environmental practitioners starting to work with rapid molecular identification using DNA or eDNA. The e-book presents step-by-step techniques, essential molecular biology concepts, and flowcharts that guide users through every stage of a research or management project: from the initial idea and project planning to sampling and species identification. While the main focus is on cartilaginous fishes (Chondrichthyes), many of the concepts and methods can be applied to other groups as well.
Da amostra à identificação rápida de DNA e DNA ambiental: um fácil guia passo a passo
Keywords: Tubarões; Raias (Peixe); Elasmobrânquios; Divulgação científica; Biologia molecular; Elasmobranch fisheries; Sharks; Rays (Fishes); Fishery management; Scientific dissemination; Conservation biology; Sequence Analysis, DNA